Local Wisdom in Literacy: A Needs Analysis for Developing Culturally Relevant Reading Materials in Primary Schools - Jamiatul Hamidah; Jumadi Jumadi; Muhammad Rafiek; Fatchul Mu'in; Rusma Noortyani; Ahmad Kailani (Universitas Lambung Mangkurat, 2026)
The development of literacy in primary schools is a global priority; however, reading materials often fail to reflect local cultural contexts. In South Kalimantan, low literacy competence is influenced by the limited availability of contextualized teaching materials. This study aimed to analyze teachers’ and students’ needs for reading materials based on local wisdom in public primary schools in Banjar Regency. A mixed-methods approach was employed. Quantitative data were collected through questionnaires administered to 317 students in Grades IV, V, and VI, while qualitative data were obtained through in-depth interviews with 23 Grade V classroom teachers. The findings reveal that although government-issued textbooks are frequently used, the representation of local wisdom is extremely limited, with only 6.6% of students reporting exposure to such content. Students expressed a strong preference for visually rich, colorful books featuring folktales from their own region. Meanwhile, teachers reported difficulties in independently developing teaching materials and emphasized the urgent need for references that systematically integrate cultural values into reading instruction. It is concluded that a significant gap exists between the availability of reading materials and the actual needs in classroom practice. The development of culturally responsive reading materials is therefore essential not only to enhance students’ learning motivation but also to support the preservation of local cultural identity. This research offers a novelty approach by systematically integrating local wisdom values into Indonesian language reading materials, resulting in effective and culturally relevant learning resources for elementary school students. The practical implication of this research is the need for contextual, local wisdom-based reading materials to provide teachers with practical guidance and to maintain local culture in education.